Training on Making Vegetable and Fruit Noodles, and Assessing Their Business and Economic Value for Households in the Kembangan Subdistrict - Astuti, Retno Puji; Indriawati, Fitri (Edumedia Solution, 2025)
This Community Service activity aims to empower housewives and PKK members in Kembangan Subdistrict through entrepreneurship training based on healthy food. According to data from the Ministry of Cooperatives and SMEs, Micro, Small, and Medium Enterprises (MSMEs) contribute 60.5% to the national GDP, indicating their great potential in supporting economic growth. In addition, Indonesia ranks second in the world for instant noodle consumption, and the rising public awareness of healthy eating presents a promising business opportunity. The main problems faced by the partners include a lack of knowledge and skills to start a business and difficulties in calculating the cost of goods sold and setting selling prices. This program offers solutions through: (1) socialization on the importance of entrepreneurship, (2) training in the production of vegetable- and fruit-based noodles, and (3) training in cost calculation and pricing. The activity is expected to improve the entrepreneurial capacity of the partners and foster the development of sustainable home-based businesses.